Crown characteristics of interior western U.S. conifers with implications for canopy fire hazard evaluation - Ex, Seth, author; Smith, Frederick, advisor; Battaglia, Michael, committee member; Dickinson, Yvette, committee member; Ryan, Michael, committee member; Steingraeber, David, committee member (Colorado State University. Libraries, 2014)
Tree crown characteristics are important determinants of forest stand features such as their potential to sustain canopy fire. There are characteristic differences between crowns of shade tolerant and shade intolerant conifer species: shade tolerant conifers generally have longer, fuller crowns than intolerant species. In this work, I investigated the response of vertical foliage distribution to stand density for a suite of western U.S. conifer species of varying shade tolerance and interpreted results in terms of canopy fire hazard evaluation. In addition, I evaluated whether diameter-based foliage area allometries differ between geographic areas in the interior western U.S. in order to gain insight into the extent that local allometries can be applied outside their area of origination. I found shade tolerant tree species maintained a greater proportion of their foliage in low light environments than intolerant species. This was consistent with lesser sensitivity of crown ratio to increasing stand density for tolerant compared to intolerant conifers. Regardless of species shade tolerance or stand density, the center of foliage mass within crowns was nearly always above the crown midpoint. Foliage mass was shifted upward and concentrated in closed-canopy forest stands compared to open-canopy woodland stands, which is consistent with greater light competition in closed-canopy stands. Foliage area allometries differed between geographic areas, and differences were species-specific. Using realistic depictions of the vertical distribution of crown fuels in a canopy fire hazard evaluation procedure resulted in dramatic increases in estimated canopy bulk density for stands, with associated increases in estimated potential fire behavior.
Keywords: forest management; wildfire; stand structure; fuel profile; silviculture; crown architecture